(untitled) (Annals of Medical Research, 2023)
Aim: Breast cancer is the most diagnosed cancer in women’s lives with a ratio of 1/8. Upadacitinib is the third selective Jak-1 inhibitor approved for RA. Upadacitinib approved by the FDA for rheumatoid arthritis effective treatment. The PD29 peptide, with its 29 amino acid sequence, it was target to especially pulmonary fibrosis. Also, PD29 is responsible for extracellular regulation in pulmonary fibrosis. In this study was aimed to investigate of the selective Jak-1 inhibitor as upadacitinib (Upa) and PD-29 on proliferation, inflammation, and oxidative stress effects in breast cancer cell line MCF-7. Materials and Methods: Experiments were performed to examine the anti-proliferative, anti-oxidative and anti-inflammatory effects of Upadacitinib and PD29. Jak-1, jak-2, jak-3, and IL-6 mRNA levels were determined by the q-RTPCR method; protein of IL-6 level was observed with ELISA. In addition, total oxidant and total antioxidant status were determined by the spectrophotometric method. Results: Compared to the control just Upadacitinib decreased cell proliferation. Upadacitinib and PD29 decreased Jak-1, Jak-2, Jak-3, and IL-6 mRNA levels significantly. Compared to the control, just Upadacitinib and Upadacitinib + PD29 decreased IL-6 protein levels significantly. There is no significance between the control and PD29 for IL-6 protein levels. In Upadacitinib group, TOS level was lower compared to control, significantly, PD29, and Upadacitinib + PD29 compared to the control. TAS level was higher in in Upadacitinib and Upadacitinib + PD29 group compared to the control. There is no significance in PD29 (0.920 ± 0.055) group for TOS levels. Conclusion: Upadacitinib and PD29 have potential targeted therapy for anti-oxidant and anti-inflammatory effects on breast cancer. In this context, it can be said that Upadacitinib and PD29 may have effective for breast cancer.